What drives the recent surge in inflation? The historical decomposition roller coaster - Drago Bergholt; Fabio Canova; Francesco Furlanetto; Nicolò Maffei-Faccioli; Pål Ulvedal (Norges Bank, 2024)
What drives the recent inflation surge? To answer this question, one must decompose inflation fluctuations into the contribution of structural shocks. We document how whimsical such a historical shock decomposition can be in standard vector autoregressive (VAR) models. We show that the deterministic component of the VAR tends to be imprecisely estimated, making the shock contributions poorly identified under general conditions. Our preferred approach to solve this problem- the single-unit-root prior-can massively shrink the uncertainty around the estimated deterministic component. Once this uncertainty is taken care of, demand shocks unambiguously appear as the main drivers of the inflation surge in the United States, the euro Area, and in four small open economies.
hdl:11250/3172780
Keywords: C11; C32; E32; 330; Bayesian vector autoregression; deterministic component; single unit root prior; inflation dynamics